Chaotic Structure of the BRIC Countries and Turkey’s Stock Market - Günay, Samet (International Journal of Economics and Financial Issues, 2015)
In this study, the parameters of chaos are analyzed for the leading emerging stock markets: Brazil, Russia, India, China, and Turkey (BRIC-T). As chaos has properties such as nonlinearity, sensitivity to initial conditions, and fractality, we performed different methods to identify the existence of the chaos in stock index returns of the BRIC-T countries, using the Brock-Dechert-Scheinkman (BDS) test, the Largest Lyapunov exponent and the Box-Counting method. Although there is widespread interest in chaos in finance theory, previous studies have neglected the long memory issue in their filtering model of nonlinear behaviors. Due to the fact that the Rescaled Range (R/S) analysis and Smith’s (2005) modified GPH test indicated long memory in the index returns, we filtered the linear structure of the returns using the methods (ARFIMA, FIGARCH, FIEGARCH) which take long memory into account. Though the results have some significant evidence of chaos, the findings are too weak to support the presence of chaos in the stock markets of BRIC-T countries. Keywords: Chaos, Fractals; Largest Lyapunov exponent; BDS Test; Fractal Dimension JEL Classifications: C14; C22; G10